Barriers and drivers of physical activity participation among older adults in Malaysia: a systematic review - Minhat, Halimatus Sakdiah; Wan Ghazali, Wan Syahirah; Mud Shukri, Muhammad Ikhwan; Noor, Norhafizah Mohd; Baharudin, Mohd Hafiidz; Yuanyuan, Zhao; Adnan, Raja Nurzatul Efah Raja (Universiti Putra Malaysia Press, 2024)
Introduction: Ageing is commonly linked with physical inactivity. This review was performed to identify the factors associated with participation in physical activity among older adults in Malaysia. Methods: A systematic review was conducted using five databases; Pubmed, Sagepub, Scopus, Cochrane Library and Science Direct. Observational and intervention studies published between January 2010 and December 2020 were included, with Malaysian older adults aged 55 years and older being the main subject. Results: A total of 9 articles were included in the review. Analysis was guided by the Social Ecological Model for Health Promotion. The review had successfully identified gender, age, education level, health reasons, ethnicity and attitude as intrapersonal factors, social support (friend) and marital status as interpersonal factors, and locality as well as availability of facilities as environmental factors. Conclusions: Physical activity participation among Malaysian older adults were mainly determined by intrapersonal factors, particularly gender, health condition and educational level.